Female Sexuality Portrayed in the Scarlet Letter and its Influence in Contemporary Works such as the Handmaid´s Tale - Gómez-Tembleque Solís, Alberto (Journal of Artistic Creation and Literary Research, 2025)
The characters, situations and dilemmas presented in The Handmaid‘s Tale are a rich re-elaboration and upgrading of a topic that had been discussed a long time before Margaret Atwood published it in 1985. Back in 1850, Nathaniel Hawthorne encapsulated the vicissitudes and strong emotional connotations of a topic as delicate as female sexuality. While The Scarlet Letter punishes sexual intercourse and exposes the female sex as a living proof of the devil‘s mission to tempt us and lure us into sinning, The Handmaid‘s Tale takes this idea and deforms it to the point where some women are only fitted to be ―two-legged wombs, that‘s all: sacred vessels, ambulatory chalices. This essay will show how female sexuality is treated in both works and how women are depicted as the sinful figures that, in these two cases, embody maternity.